Nanoscale physical analysis of localized breakdown events in HfO2/SiOX dielectric stacks : a correlation study of STM induced BD with C-AFM and TEM - Shubhakar, K. (2013)
The study of scanning tunneling microscopy (STM) induced localized degradation and polarity dependent breakdown (BD) of HfO2/SiOx dielectric stacks is presented in this work, together with a correlated investigation of the BD locations by transmission electron microscopy (TEM). The localized dielectric BD events are also analysed using conductive-atomic force microscopy. The analysis of the degradation and breakdown phenomenon has been performed from a macroscopic (device) level to a localized nanometer scale BD location. A new technique is adopted to induce the degradation and BD of the HfO2/SiOx dielectric stacks locally using a combined STM/scanning electron microscopy nano-probing system. The BD locations were identified on blanket wafers and gate electrode area of the dielectric, and the sample containing these regions was prepared using focused ion beam for the physical analysis using TEM. This method of analysis is very useful in studying the nature of the BD events in dielectrics with and without the gate electrode, elucidating the role of the gate electrode in dielectric BD events.